Takeoff Capacity Improvement at Soekarno-hHatta Airport Using Arena Simulation - Harbi Putra (NIM : 13413014), Hasbi
Indonesian flights tend to experience growth from year to year. This can be seen from aircraft movement that has an average growth of 3.49% from 2011 to 2015. Soekarno-Hatta Airport is the busiest airport in Indonesia to acommodate 381,649 aircraft movement in 2015 which amounted to 23% of all aircraft movement in Indonesia . The publication from LPPNPI states that the capacity of Soekarno-Hatta Airport currently can reach 72 units of aircraft per hour. With the continuous growth of aircraft movement production it is necessary to make improvements to Soekarno-Hatta Airport to increase capacity. Therefore it is necessary to simulate the movement of aircraft at Soekarno-Hatta Airport to know the capacity change if some improvement is implemented. This research is expected to provide the best solution to increase the capacity of Soekarno-Hatta Airport. In this study Arena Simulation software is used to create a simulation model. The simulation model created is the take-off aircraft movement. This model will be combined with the landing aircraft movement simulation model. In the simulation model, data are used such as the time between departures of aircraft, airplane speed, road length and taxiing routes as input to the simulation. The output of the simulation being observed is the average waiting time and the average length of the aircraft queue on each road segment and on the runway. By looking at the performance of existing systems, improvement will be made in the proposed model. The improvement options are to replace the airport operating system from mixed operation to segregated operation. In addition it can also add some taxiway roads. With the implementation of such improvements, the capacity of airports can increase.